Lack of a Cytoplasmic RLK, Required for ROS Homeostasis, Induces Strong Resistance to Bacterial Leaf Blight in Rice - Yoo, Youngchul; Park, Jong-Chan; Cho, Man-Ho; Yang, Jungil; Kim, Chi-Yeol; Jung, Ki-Hong; Jeon, Jong-Seong; An, Gynheung; Lee, Sang-Won (Frontiers in Plant Science, 2018)
Many scientific findings have been reported on the beneficial function of reactive oxygen species (ROS) in various cellular processes, showing that they are not just toxic byproducts. The double-edged role of ROS shows the importance of the regulation of ROS level. We report a gene, rrsRLK (required for ROS-scavenging receptor-like kinase), that encodes a cytoplasmic RLK belonging to the non-RD kinase family. The gene was identified by screening rice RLK mutant lines infected with Xanthomonas oryzae pv. oryzae (Xoo), an agent of bacterial leaf blight of rice. The mutant (ΔrrsRLK) lacking the Os01g02290 gene was strongly resistant to many Xoo strains, but not to the fungal pathogen Magnaporthe grisea. ΔrrsRLK showed significantly higher expression of OsPR1a, OsPR1b, OsLOX, RBBTI4, and jasmonic acid-related genes than wild type. We showed that rrsRLK protein interacts with OsVOZ1 (vascular one zinc-finger 1) and OsPEX11 (peroxisomal biogenesis factor 11). In the further experiments, abnormal biogenesis of peroxisomes, hydrogen peroxide (H2O2) accumulation, and reduction of activity of ROS-scavenging enzymes were investigated in ΔrrsRLK. These results suggest that the enhanced resistance in ΔrrsRLK is due to H2O2 accumulation caused by irregular ROS-scavenging mechanism, and rrsRLK is most likely a key regulator required for ROS homeostasis in rice.